Zeros for the Gradients of Weakly A-Harmonic Tensors. (12th May 2014) - Tong, Yuxia; Gu, Jiantao; Zheng, Shenzhou
Abstract : The Caccioppoli inequality of weakly A -harmonic tensors has been proved, which can be used to consider the weak reverse Hölder inequality, regularity property, and zeros of weakly A -harmonic tensors.